Circular economy is game-changing municipal wastewater treatment technology towards energy and carbon neutrality - Zhang, Xiaoyuan; Liu, Yu (Chemical engineering journal (Lausanne, Switzerland : 1996), 2022)
•Municipal wastewater is a regenerative resource of freshwater, energy and nutrients.•Municipal wastewater reclamation is need-driven to cater for various scenarios.•A paradigm shift is necessary for sustainable water, energy and resource management.•AnMBR is unique for addressing the water-energy-resource-climate change nexus.•Circular economy drives energy- and carbon–neutral wastewater reclamation. With gradual transformation of global linear economy to circular economy, the present municipal wastewater treatment processes designed with the philosophy of take-make-dispose are facing incredible economic and environmental pressures due to high energy consumption, emission of greenhouse gases, waste generation etc. In such a situation, “we cannot solve our problems with the same thinking we used when we created them” as said Albert Einstein. Therefore, this article intends to trigger discussion on how circular economy is to game-change municipal wastewater treatment technology towards energy and carbon neutrality. As illustrated with anaerobic MBR as an example, municipal wastewater indeed is a regenerative resource of freshwater, energy and mineral nutrients rather than a waste. This will lead to a paradigm shift of municipal wastewater engineering from simple treatment to recovery and reuse of multiple resources for synergistically addressing the water-energy-resource-greenhouse gases nexus in an environmentally and economically sustainable manner, with the ultimate goals of energy and carbon neutrality in municipal wastewater reclamation.